2014
DOI: 10.5194/isprsarchives-xl-2-w3-175-2014
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Statistical Characteristics of Frosts in Iran

Abstract: ABSTRACT:To model and map the statistical characteristics of frost in Iran, the data related to the minimum daily temperature for a 15-year period (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) was obtained from Iran Meteorological Organization. Then using multivariate regression models, the relationship among five statistical characteristics, i.e. the mean Julian day of the first frost, mean Julian day of the last frost, mean number of frost days per year, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This is directly related to elevation and location of these stations, their situation in the position of external synoptic systems, physical and geomorphological functions and local weather. Mahmoudi (2014) showed that temperatures over highland areas which reach up to 4200 m above the sea level were always greater than 0 • C or below 0 • C at some point of the year and, additionally, the coastal zone of southern Iran had no frost. Elevation becomes the main factor for the frequency of frost incidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is directly related to elevation and location of these stations, their situation in the position of external synoptic systems, physical and geomorphological functions and local weather. Mahmoudi (2014) showed that temperatures over highland areas which reach up to 4200 m above the sea level were always greater than 0 • C or below 0 • C at some point of the year and, additionally, the coastal zone of southern Iran had no frost. Elevation becomes the main factor for the frequency of frost incidence.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the earliest autumn frost and the latest spring frost occur in the Taftan Mountains, and the latest autumn frost and the earliest spring frost occur within the western and southeastern regions. Mahmoudi (2014) examined the use of multivariate regression trends, modelled the relationship among five statistical characteristics (i.e., the mean Julian day of the first frost, mean Julian day of the last frost, suggested range of frost days each year, the duration of the frost period and the average period of the growing season by way of three geo-climate elements: elevation, longitude and latitude). The results showed that the temperature of the highland regions which reached up to 4200 m above sea level was usually 0 • C and colder throughout the year, and additionally, the coastal strip of southern Iran had no frost.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of frost events is influenced by a range of factors. Typically, locations situated at higher latitudes and altitudes are more susceptible to experiencing more frequent frost events compared to those situated at lower latitudes and altitudes (Kalma et al, 1992; Mahmoudi, 2014). Moreover, the climatic conditions, such as temperature, precipitation, atmospheric circulation, and other factors, significantly affect the frequency and duration of FDs and FFPs (Seok et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in frost events are influenced by a multitude of factors, including geographical position, atmospheric circulation patterns and meteorological variables such as air temperature, humidity, wind and cloud cover (Kalma et al, 1992; Mahmoudi, 2014; Masaki, 2022; Seok et al, 2017; Shen et al, 2014). In the absence of warming, theoretical frameworks and empirical studies associate anomalous frost timing with atmospheric circulation anomalies.…”
Section: Introductionmentioning
confidence: 99%